Antibiotic-Induced Changes in Pigment Accumulation, Photosystem II, and Membrane Permeability in a Model Cyanobacterium - Yalcin, Yavuz S.; Aydin, Busra N.; Sayadujjhara, Mst; Sitther, Viji (Frontiers in Microbiology, 2022)
Fremyella diplosiphon is a well-studied a model cyanobacterium for photosynthesis due to its efficient light absorption potential and pigment accumulation. In the present study, the impact of ampicillin, tetracycline, kanamycin, and cefotaxime on pigment fluorescence and photosynthetic capacity in Fremyella diplosiphon strains B481-WT and B481-SD was investigated. Our results indicated that both strains exposed to kanamycin from 0.2 to 3.2 mg/L and tetracycline from 0.8 to 12.8 mg/L enhanced growth and pigment accumulation. Additionally, B481-SD treated with 0.2 to 51.2 mg/L ampicillin resulted in a significant enhancement of pigment fluorescence. A detrimental effect on growth and pigmentation in both the strains exposed to 6.4 to 102.5 mg/L kanamycin and 0.8-102.5 mg/L cefotaxime was observed. Detection of reaction oxygen species revealed highest levels of oxidative stress at 51.2 and 102.5 mg/L kanamycin for B481-SD and 102.5 mg/L for B-481-WT. Membrane permeability detected by lactate dehydrogenase assay indicated maximal activity at 0.8 mg/L ampicillin, kanamycin, and tetracycline treatments on day 6. Abundant vacuolation, pyrophosphate, and cyanophycin granule formation were observed in treated cells as a response to antibiotic stress. These findings on the hormetic effect of antibiotics on F. diplosiphon indicate that optimal antibiotic concentrations induce cellular growth while high concentrations severely impact cellular functionality. Future studies will be aimed to enhance cellular lipid productivity at optimal antibiotic concentrations to disintegrate the cell wall, thus paving the way for clean green energy applications.